Quantifying spatiotemporal dynamics of urban building and material metabolism by combining a random forest model and GIS-based material flow analysis - Mao, Ting; Liu, Yupeng; Chen, Wei-Qiang; Li, Nan; Dong, Nan; Shi, Yao (Frontiers in Earth Science, 2022)
Understanding building metabolism is critical for guiding urban resource management and addressing challenges in urban sustainable development. Key attributes of buildings, including geolocation, footprint, height, and vintage, are crucial to characterize spatiotemporal patterns of building metabolism but are often difficult to obtain. In this study, we took Shenzhen——whose urbanization over the past three decades is unprecedented in China and even around the world——as an example to develop a city-level building dataset based on a random-forest model and quantify the spatiotemporal patterns of material metabolism at relatively high spatial resolution (in 500mx500m grids) by combing material flow analysis (MFA) with geographic information system (GIS). The results show that the volume of Shenzhen grew from a small town with 281.02 x106 m3 of buildings in the 1990s to a mega-city with 3585.49 x106 m3 of buildings in 2018 and expanded outward from downtown to suburban areas. The urban ‘weight’ (material stock) increased from 92.69 Mt in the 1990s to 1667.8 Mt in 2018 and tended to be saturated, with an average growth rate of 9.5% per year. Spatially, the south-central areas were the largest container of material stocks and generated the most demolition waste. The spatially explicit maps of building three-dimensional (3-D) form and vintage provide detailed information for architectural conservation and could support the decision-making for urban renewal planning. The spatiotemporal patterns of in-use material stocks and potential generation of construction and demolition waste (CDW) characterized by the dynamic and spatial model provide a benchmark of environmental risk assessment and potential secondary resources to reduce ‘original’ material consumption, which could help alter urban renewal to an environmental-friendly and sustainable trajectory.